The Early Diagnostic Value of Serum Interleukin-8 in Esophagogastric Junction Adenocarcinoma. (29th April 2021) - Li, Zheng; Xu, Haijie; Yu, Jiaming; Liu, Cantong; Zheng, Chunwen; Zeng, Ruijie; Xu, Liyan; Li, Enmin; Peng, Yuhui; Xu, Yiwei
Background: Esophagogastric junction adenocarcinoma (EJA) is one of the most common malignant tumors of digestive tract with high mortality worldwide. Given a lack of early diagnosis biomarkers, the prognosis of EJA is poor. Non-invasive biomarkers for early-stage EJA are urgently required. Objective: We aimed at evaluating the early diagnostic value of serum interleukin-8 (IL-8) level in EJA patients. Methods: The IL-8 mRNA expression data were analyzed based on the stomach cardia adenocarcinoma samples of The Cancer Genome Atlas (TCGA) database. Enzyme-linked immunosorbent assay (ELISA) was used to measure the concentration of serum IL-8 in 95 EJA patients and 95 normal controls enrolled from 2 different cancer hospitals. The diagnostic accuracy of serum IL-8 was evaluated by applying Mann-Whitney U test and receiver operating characteristic (ROC) curve. Results: The mRNA expression levels and serum levels of IL-8 in EJA group were significantly higher than those in the normal group (all P < 0.001). The areas under the ROC curve (AUC) were 0.661 (95% CI, 0.583-0.740) and 0.745 (95% CI, 0.606-0.885), with the sensitivities of 43.2% (95% CI, 33.2%-53.7%) and 66.7% (95% CI, 46.0%-82.8%) and the specificities of 87.4% (95% CI, 78.6%-93.1%) in EJA group and early-EJA group, respectively, when the optimal cutoff value was 109.086 pg/mL. The clinical data analysis showed there were significant correlations between patient genders, depth of invasion, lymph node metastasis, TNM stage and the serum level of IL-8 (all P < 0.05). Conclusions: Serum IL-8 represents a potential diagnostic biomarker to identify early-stage EJA.